High-performance modified LDH for green one-pot synthesis of pyrido[2,3-d]pyrimidines - Sarieh Momeni; Ramin Ghorbani-Vaghei (Heliyon)
This study introduces a new nano catalyst tailored for the eco-friendly synthesis of pyrido[2,3-d]pyrimidine via a three-component one-pot reaction involving benzaldehydes, malononitrile, and uracil. To achieve this objective, we anchored copper acetate onto the surface of layered double hydroxides modified with 1,3‑benzenedisulfonyl amide (BDSA) (LDH@PTRMS@BDSA@Cu(NO3)2), which exhibited remarkable activity and selectivity. The main benefits of this method include high product yield, swift reaction times, straightforward purification, catalyst reusability, and the employment of a mild reaction process. Furthermore, the catalyst maintained its effectiveness even after being recycled four times without notable degradation in catalytic performance.